2003
DOI: 10.1577/1548-8454(2003)065<0060:teouty>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Using Two-Year-Old Male Coho Salmon in Hatchery Broodstock on Adult Returns

Abstract: We conducted an experiment comparing the age at maturity of hatchery coho salmon Oncorhynchus kisutch sired with 2% or 100% age-2 jacks and released at two smolt sizes. Progeny sired by 100% age-2 males returned significantly more age-2 jacks than did those sired with 2% age-2 males. However, the survival and mean length of age-3 fish was similar for the two groups. Significantly more age-2 returns were produced by releasing larger (34-40 g) smolts rather than smaller (23-28 g) ones, but smolt size did not aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Others observed that among half-pounders, mature fish were generally the largest individuals of the group: >349 mm FL (Kesner and Barnhart 1972) and 380 mm FL (Everest 1973). Appleby et al (2003) demonstrated that the frequency of jacks within a co-hort of Coho Salmon could be increased by increasing smolt size. Incidence of sexual maturity among half-pounders may respond similarly to increasing smolt size and, thus, to increasing freshwater productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Others observed that among half-pounders, mature fish were generally the largest individuals of the group: >349 mm FL (Kesner and Barnhart 1972) and 380 mm FL (Everest 1973). Appleby et al (2003) demonstrated that the frequency of jacks within a co-hort of Coho Salmon could be increased by increasing smolt size. Incidence of sexual maturity among half-pounders may respond similarly to increasing smolt size and, thus, to increasing freshwater productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Length at release influences survival to adulthood in hatchery steelhead Oncorhynchus mykiss (Larson and Ward 1955;Royal 1972;Tipping 1997) and sea-run cutthroat trout O. clarkii (Tipping 1986), while survival to adulthood in hatchery coho salmon O. kisutch is generally not affected by smolt length (Hager and Noble 1976;Hopley et al 1993;Appleby et al 2003;Tipping 2008). The smolt length of Chinook salmon O. tshawytscha has been shown to affect adult survival, although there is limited published literature on the subject (Fowler and Banks 1980;Bilton 1984;Martin and Wertheimer 1989;Beckman et al 1998).…”
mentioning
confidence: 99%
“…This is in part because they are not genetically distinct and because the interplay between genetic and environmental factors determines the 'decision' whether or not an individual will mature early. Evidence for strong heritability in age-at-maturity comes from quantitative genetic studies (Hankin et al 1993;Heath et al 1994;Heat et al 2002) and measures at the population level (Hard et al 1985, Appleby et al 2003. Physiological traits mediated by environmental conditions (e.g., body size, fatness), can trigger early male maturation (Vøllestad et al 2004;Shearer et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…They may benefit from reduced predation or other forms of ecological selection during reproduction (Quinn et al 2001). Nevertheless, jack males often represent a small portion of breeding populations of sockeye, coho and Chinook salmon (Carlson et al 2004, Appleby et al 2003, Myers et al 1998). This may partly reflect disadvantages of small size and reduced access to females during reproduction (Carlson et al 2004), although the natural relative breeding success of jack and adult male Pacific salmon has received very little attention.…”
Section: Introductionmentioning
confidence: 99%